If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7y + 7 = 35 Reorder the terms: 7 + -7y = 35 Solving 7 + -7y = 35 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -7y = 35 + -7 Combine like terms: 7 + -7 = 0 0 + -7y = 35 + -7 -7y = 35 + -7 Combine like terms: 35 + -7 = 28 -7y = 28 Divide each side by '-7'. y = -4 Simplifying y = -4
| -3(x-7)=18 | | -5=6(3)-27 | | 25x^4-60c^2+36=0 | | 2/x-3=8/3x-3 | | 3=6(-5)-27 | | (12a^2b^-2)/(8a^-3b^7) | | 5x+4=x-20 | | 12a^2b^-2/8a^-3b^7 | | logx=-.29 | | a=84+2(10) | | 15n-1+5=0 | | a=54+5(10) | | a=84+2(1000) | | .6c+11=5 | | a=54+5(1000) | | 2(y-5)=4y+10 | | 1/2•6 | | a=54+5(5) | | 6c-7=17 | | y-b=kx | | A=84+2(20) | | 6(7x+1)=43 | | y-b/k=kx/k | | 1.25(x+75)=250 | | 4x-(3x+15)=30 | | A=54+5(20) | | 5k^2=3-2k | | 3x-9x=21 | | 2.4e+12= | | 8=4n-16 | | 2x+7=-3x+17 | | 9x+4x-x=48 |